Y = -3x + 5
5x - 4y = -3
5x - 4(-3x + 5) = -3
5x + 4(3x) - 4(5) = -3
5x + 12x - 20 = -3
17x - 20 = -3
+ 20 + 20
17x = 17
17 17
x = 1
y = -3x + 5
y = -3(1) + 5
y = -3 + 5
y = 2
(x, y) = (1, 2)
Answer: a. 0.6759 b. 0.3752 c. 0.1480
Step-by-step explanation:
Given : The long-distance calls made by the employees of a company are normally distributed with a mean of 6.3 minutes and a standard deviation of 2.2 minutes
i.e.
minutes
minutes
Let x be the long-distance call length.
a. The probability that a call lasts between 5 and 10 minutes will be :-
![P(5](https://tex.z-dn.net/?f=P%285%3CX%3C10%29%3DP%28%5Cdfrac%7B5-6.3%7D%7B2.2%7D%3C%5Cdfrac%7BX-%5Cmu%7D%7B%5Csigma%7D%3E%5Cdfrac%7B10-6.3%7D%7B2.2%7D%29%5C%5C%5C%5C%3DP%28-0.59%3CZ%3C1.68%29%5C%20%5C%20%5C%20%5C%20%5Bz%3D%5Cdfrac%7BX-%5Cmu%7D%7B%5Csigma%7D%5D%5C%5C%5C%5C%3DP%28z%3C1.68%29-%281-P%28z%3C0.59%29%29%5C%5C%5C%5C%3D0.9535-%281-0.7224%29%5C%20%5C%20%5C%20%5C%20%5B%5Ctext%7Bby%20z-table%7D%5D%5C%5C%5C%5C%3D0.6759)
b. The probability that a call lasts more than 7 minutes. :
![P(X>7)=P(\dfrac{X-\mu}{\sigma}>\dfrac{7-6.3}{2.2})\\\\=P(Z>0.318)\ \ \ \ [z=\dfrac{X-\mu}{\sigma}]\\\\=1-P(Z](https://tex.z-dn.net/?f=P%28X%3E7%29%3DP%28%5Cdfrac%7BX-%5Cmu%7D%7B%5Csigma%7D%3E%5Cdfrac%7B7-6.3%7D%7B2.2%7D%29%5C%5C%5C%5C%3DP%28Z%3E0.318%29%5C%20%5C%20%5C%20%5C%20%5Bz%3D%5Cdfrac%7BX-%5Cmu%7D%7B%5Csigma%7D%5D%5C%5C%5C%5C%3D1-P%28Z%3C0.318%29%5C%5C%5C%5C%3D1-0.6248%5C%20%5C%20%5C%20%5C%20%5B%5Ctext%7Bby%20z-table%7D%5D%5C%5C%5C%5C%3D0.3752)
c. The probability that a call lasts more than 4 minutes. :
![P(X](https://tex.z-dn.net/?f=P%28X%3C4%29%3DP%28%5Cdfrac%7BX-%5Cmu%7D%7B%5Csigma%7D%3C%5Cdfrac%7B4-6.3%7D%7B2.2%7D%29%5C%5C%5C%5C%3DP%28Z%3C-1.045%29%5C%20%5C%20%5C%20%5C%20%5Bz%3D%5Cdfrac%7BX-%5Cmu%7D%7B%5Csigma%7D%5D%5C%5C%5C%5C%3D1-P%28Z%3C1.045%29%5C%5C%5C%5C%3D1-0.8520%20%5C%20%5C%20%5C%20%5B%5Ctext%7Bby%20z-table%7D%5D%5C%5C%5C%5C%3D0.1480)
Answer:1387.96
Please mark me as Brainliest!
Step-by-step explanation:
Answer:
Step-by-step explanation:
Given : Expression = ![-2xy+3x-2xy+3x](https://tex.z-dn.net/?f=-2xy%2B3x-2xy%2B3x)
Simplifying the expression :
Step 1. Write the expression = ![-2xy+3x-2xy+3x](https://tex.z-dn.net/?f=-2xy%2B3x-2xy%2B3x)
Step 2. Add the similar elements: ![3x+3x=6x](https://tex.z-dn.net/?f=3x%2B3x%3D6x)
= ![-2xy-2xy+6x](https://tex.z-dn.net/?f=-2xy-2xy%2B6x)
Step 3. Add the similar elements: ![-2xy-2xy=-4xy](https://tex.z-dn.net/?f=-2xy-2xy%3D-4xy)
= ![-4xy+6x](https://tex.z-dn.net/?f=-4xy%2B6x)
Therefore,
is the simplified form of ![-2xy+3x-2xy+3x](https://tex.z-dn.net/?f=-2xy%2B3x-2xy%2B3x)
this is kinda easy and im gonna assume that the 4 is a exponent cuz f(2)=2(3)^4 then f=81